Thymoquinone harbors protection against Concanavalin A‐induced behavior deficit in BALB/c mice model. Issue 3 (2nd July 2020) - Nazir, Sadia; Farooq, Rai Khalid; Khan, Hina; Alam, Tahseen; Javed, Aneela
Abstract: Global health estimates indicated approximately 322 million people living with depression. Rising cost of depressive illness treatment and non‐responsiveness to existing therapies demand continued research to explore new and more potent therapies. Exploring the potential of natural compounds for their potent antidepressant potentials is becoming topic of interest for scientists. Anti‐inflammatory activity of thymoquinone, the active ingredient of Nigella sativa, has been well documented. Current study tested thymoquinone for its antidepressant effect in a Concanavalin A (Con A)‐induced depressive‐like behavior in BALB/c mice. Thymoquinone successfully protected against Con A‐induced behavioral despair and anxiety‐like behavior. Reduced grooming behavior as a function of Con A treatment, was also reinstated. Underlying mechanism responsible for antidepressant activity of thymoquinone was analyzed by molecular docking. Thymoquinone interacts in halogen‐binding pocket (HBP) of serotonin reuptake transporter indicating its potential as serotonin reuptake inhibitor. Results of current study anticipate thymoquinone as a potential antidepressant drug candidate. Practical applications: Black seeds of Nigella sativa are consumed with traditional and religious reference since centuries. Thymoquinone, active, and abundant component of Nigella sativa, has shown positive effects in multiple studies against arthritis, asthma, hepatic injury, neurodegeneration, and cancer owing to its immunomodulatory and anti‐inflammatory attributes. Considering inflammation as one of central components involved in pathophysiology of major depressive disorder, thymoquinone has been evaluated in current study for its antidepressant potential. Positive results of current study propose thymoquinone as an affordable, natural antidepressant drug candidate with better safety profile than currently available antidepressant regimes. Thymoquinone might provide benefits against inflammation‐related sickness behavior that is associated with poorer outcome of clinical depression, thus, paving the way for effective drug development against treatment‐resistant depression. Abstract : Given the well‐known anti‐inflammatory activity of thymoquinone, current study reports successful reversal of Concanavalin A ‐induced behavioral despair including anxiety‐like, depressive‐like and grooming behavior in BALB/c mice. Docking analyses propose interaction of thymoquinone in halogen binding pocket of serotonin reuptake transporter, proposing its potential as serotonin reuptake inhibitor.